Strategi Gerakan Pariwisata Mangrove dalam Mewujudkan Perilaku Ekosentrisme - Aimie Sulaiman; Komang Jaka Ferdian; La Ode Muhamad Muliawan (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
The ecological damage to the coast of Bangka has forced the community to carry out environmental conservation movements to improve their marine ecology. The environmental movement carried out by the HKm Gempa 01 Group in Kurau Barat Village is an ecocentrism activity that is the antithesis of anthropocentrism behavior that has damaged the environment in the Bangka Belitung Islands. On that basis, this research was conducted to analyze and know the Ecocentrism-based Mangrove Tourism Movement Strategy. This study uses a qualitative descriptive method with data collection techniques using observation, interviews with purposive sampling techniques, and documents, while the analysis technique uses data triangulation. The results showed that the HKm Gempa 01 Group mobilized three stakeholders, namely the government, the community, and tourists, to manage the Mangrove area based on ecocentrism behavior. The success of the management of the area forms a movement strategy that can pressure three stakeholders to transform anthropocentrism behavior towards ecocentrism behavior in the management of the Munjang Kurau Mangrove area.